The characteristic of impacted soil by the Merapi Eruption in Plawangan Hill of Taman Nasional Gunung Merapi, Yogyakarta, Indonesia - Khan, Kamran; Wilopo, Wahyu; Sadono, Ronggo; Hermawan, Much. Taufik Tri (Journal of Degraded and Mining Lands Management, 2024)
Mount Merapi National Park (TNGM) is one of the active volcanos in Indonesia. It has past volcano eruption history since 1911 up to date. Specifically, Plawangan Hill is a part of the TNGM recently designated as Geo-heritage and has experienced volcano eruption indirectly and directly. Additionally, since the Indonesian government designates Plawangan Hill as a Geological Heritage (Geo-Heritage) location, it is crucial to determine its geological features and how they relate to the development of the vegetation there as the study’s objectives. A field survey and a soil laboratory examination were conducted to obtain the data. As a result, Plawangan Hill’s DEM was classified from very low to very high classes, while the DSM was categorized from flat to very steep slopes. Further, the results demonstrated that the pH of the soil was typically somewhat acidic (5.93–6.54). While the soil’s nitrogen content was found to be low to medium, both phosphorus and potassium levels were typically very low. The carbon-nitrogen ratio was generally categorized into the medium, while the organic C ranged from low to medium (1.44% to 3.22%). The soil’s N total, K total, organic matter, carbon content, and C-N ratio increased by the erupted material age. Additionally, it was discovered that the vegetation growth was excellent in indirect (IA) and directly affected (DA) conditions, as indicated by their diameter at breast height (Dbh) and height (H). The correlation between soil characteristics and vegetation growth differed in indirectly affected (IA) and directly affected (DA) areas. As a result, the study found that volcanic materials significantly contributed to Plawangan Hill’s soil characteristics and vegetation growth. Furthermore, this study’s findings were highly beneficial because they were one of the primary explanations for why Plawangan Hill was designated a Geo-heritage site.